Kidney transplantation in children with a compromised inferior vena cava: a unique experience at Shumakov Research Center - D. A. Saydulaev; A. A. Zharikov; A. A. Kartashev; P. M. Gadzhieva; A. R. Karapityan (Вестник трансплантологии и искусственных органов)
Compromised inferior vena cava (IVC) is a rare but life-threatening condition in low-birth-weight children who require kidney transplantation (KT) to survive.Objective: to demonstrate a comprehensive approach to KT in children with IVC atresia.Materials and methods. In the period from December 2019 to April 2024, 5 kidney transplants were performed in children with atresia or obliteration of the IVC at Shumakov National Medical Research Center of Transplantology and Artificial Organs. The average age of the children at transplantation was 4.6 ± 2.7 (from 1 to 8 years) years, body weight 13.5 ± 4 (from 8.3 to 19.5) kg. Results. Vertical midline transperitoneal approach was performed, the right lobe of the liver, as well as the accessible part of the subhepatic IVC were partially mobilized. The renal graft was positioned on the right side with the formation of venous anastomosis with the accessible part of the subhepatic IVC. All the children had primary graft function. There were no acute rejection episodes at year 1 post-transplant. The average renal graft glomerular filtration rates in recipients at 3 months and at 1 year post-transplant were 95.9 ± 9.6 ml/min per 1.73 m2 and 80.6 ± 26.2 ml/min per 1.73 m2, respectively. Conclusion. When the iliac veins and/or distal IVC are compromised, venous outflow into an accessible IVC segment is the preferred option. Transplantation in the left orthotopic position and other mentioned revascularization techniques are complex surgical techniques with a higher risk of thrombotic complications in the early postoperative period.